Giant Cystic Pneumocytoma in a Young Male: Rare Diagnostic Conundrum with Clinicoradiological and Histopathological Features - Manphool Singhal; Nishita Yadav; Pavithra Subramanian; Harkant Singh; Amanjit Bal; Arun Sharma (Indian Journal of Radiology and Imaging)
Pulmonary sclerosing pneumocytoma is a rare benign neoplasm typically seen in middle-aged women. The exact preoperative diagnosis is quite challenging considering its nonspecific clinical and radiologic features along with complex histology. Moreover, obtaining an exact histopathological diagnosis can be difficult especially with the small biopsy specimens. Most patients are generally asymptomatic with incidental detection of peripheral, homogenous, solitary pulmonary nodule. It is essential to differentiate it from other mimickers including malignant lesions as limited surgical resection is curative in these cases without adjuvant therapy. We present a rare giant cystic variant of pneumocytoma, in a young male, which was initially mimicking inflammatory myofibroblastic tumor even on preoperative histology.